Diskriminasi Usia dan Reproduksi Kekuasaan dalam Hubungan Industrial Pada Sektor Industri Manufaktur di Karawang - Natasya Tsanya Fildzah; Irwansyah Irwansyah (Jurnal Politikom Indonesiana, 2025)
Karawang is known as one of the largest manufacturing industry centers in Indonesia, with many factories owned by large companies. The phenomenon of age discrimination began to emerge because many job seekers—especially those aged 30 and over—complained about not getting job opportunities even though they had experience. The purpose of this study is to analyze how this age discrimination practice ultimately results in a power structure between employers and workers. Therefore, previous studies tend to view the attitude of age in the age recruitment process as a discriminatory policy alone, without highlighting the political coercion of workers' bargaining positions. By using qualitative methods through in-depth interviews and the theoretical framework of The Four Dimensions of Power by Mark Haugaard, this study was able to reveal that age power strengthens the company's control over young workers, which ultimately gives rise to their bargaining position and solidarity. The findings show that age discrimination is a mechanism to continue to perpetuate the inequality of power relations in industrial relations that have been maturely internalized. Thus, this study broadens the understanding of age discrimination as a manifestation of political strategy in industrial relations, and not just an administrative policy. The implications of this research highlight the need for more inclusive and equitable changes in employment regulations, as well as strengthening labor collectivity to face pressures from the capitalist system. Keywords: Age Discrimination, Political Power, Industrial Relations, Bargaining Power